Smoking and COVID 19: Analysing this controversy in a Brazilian COVID-19 Reference Centre - Bartholo, Thiago P.; Pôrto, Luís C.; Costa, Claudia H.; Lopes, Agnaldo José; Graça, Nadja P.; Chibante, Fernanda O.; Bessa, Elizabeth J. C.; Nunes, Alessandra S.; Rufino, Rogério R. (Brazilian Journal of Health and Biomedical Sciences, 2022)
Introduction: Due to the COVID-19 pandemic, it is extremely important to determine the risk factors that define patients who are more susceptible to the severe form of the disease; however, the observation of supposedly protective factors is also of great relevance. Smoking has been the subject of controversy as to whether it is a protective factor or a risk factor for COVID-19. Objective: To assess how smokers behave within the context of the COVID-19 pandemic. Patients and methods: The participants in this study were a spontaneously recruited sample from the Rio de Janeiro State University COVID-19 Reference Centre, between March and May 2020. All patients underwent clinical, laboratory, and nasal swabs for the Sars-Cov-2 PCR investigation. Whenever it was the necessary case, patients were referred to hospitalization. Results: A total of 4,636 patients with suggestive symptoms of COVID were evaluated. There was 230 (4.9%) smokers in this group; there is a 10.3% smoking prevalence in the state of Rio de Janeiro as described in 2018. A number of 2,246 patients (48.6% of the total sample) were diagnosed with COVID-19, only 82 of these (3.7% of the total positive COVID) were smokers. Only 1 (0.01%) of the smokers with COVID-19 needed hospitalization. As far as the assessed symptoms, smokers showed fewer symptoms during the disease. Conclusion: The study suggests that smokers have fewer symptoms (mild or asymptomatic symptoms) and that there is a need to expand specific testing for that group.